Pengembangan Platform Digital Krama Adat untuk Transparansi dan Monitoring Iuran di Desa Adat Duku Pulu Kaja, Tabanan-Bali - Indriyani Indriyani; Paula Dewanti; I Gusti Bagus Agung Kusuma Atmaja (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to develop a Digital Krama Adat Platform to enhance transparency and monitoring of traditional community contributions in Desa Adat Duku Pulu Kaja, Tabanan, Bali, which has a strong traditional social structure. The main problems faced by partners include low transparency and accuracy in contribution recording, limited community participation, and the absence of an integrated information system. The methods used include needs analysis, web-based platform development, digital literacy training, participatory mentoring, and data digitalization. The results show the successful implementation of a digital platform with features such as an admin dashboard and resident portal, real-time transaction recording, automatic reporting, and self-monitoring. The system reduces recording errors from 15% to 2% and increases community trust. This activity demonstrates that integrating technology with local governance structures can strengthen accountability, participation, and good governance in traditional communities.